The Singer’s Struggles to Fight for the Gender Equality in Lea Salonga’s Reflection Song - Caesaria Omega Putri Pesik; Siti Isminarni; Nirwan Nirwan (STIBA IEC JAKARTA, 2024)
The topic in this study is about issues of feminism, gender and stereotypes that occur in the singer’s life journey as depicted in the lyrics of the song Reflection by Lea Salonga (1998). The method used in this study is a qualitative method based on the lyrics of the song Reflection by Lea Salonga as the main data source. To analyze this song, the researcher applies feminism and sociological approaches. The results of this study concluded that the singer in the song lyric experienced a process of searching for identity while fighting for the ideal that women also have the right to stand equal to men and bear equal responsibilities without needing to feel weaker. It is hoped that this study could serve as a new reference regarding the issue of feminism and gender stereotypes in literary works